Fabrication of Organic Light Emitting Diodes (OLEDs) using the Lamination method in a Vacuum-Free Environment - Alfafa, Daris; Moraru, Daniel; Udhiarto, Arief (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
Organic Light Emitting Diodes (OLEDs) have recently become one of the fastest-growing technologies in the world. The challenge in OLED fabrication, especially larger-area OLEDs, is its relatively high costs and complexity. The lamination method at a vacuum-free environment is an approach to simplify and reduce the cost of fabrication. This paper reports our latest progress on OLEDs fabricated using the said method and condition. The processing parameters were explored and optimized. Spin coating the emissive Layer (PFO) at 1300 rpm and the anode (TC-07-S) at 3000 rpm yield the best results in terms of current conduction and success rate. Laminating the OLEDs at 160 °C, with 245 N of force, and for 30 seconds, gave the best results in terms of previously stated parameters. Furthermore, the constituting materials of the OLEDs were explored. It was found that TC-07-S as an anode, PFO as the light-emitting material, a 30-micrometer thick aluminum foil as the cathode, and Kapton as the dielectric and adhesive material yielded the best results. These results may pave the way for other innovative methods to fabricate OLEDs with a simple and affordable processes.